(untitled) - Messing, Bob (New York, 1989)
A guide to using the ancient secrets of successful management in today's careers teaches readers how to be strong managers without using force; enlist employee support, enthusiasm, and loyalty; recognize opportunities; and more.
Keywords: Executives,Nhân viên điều hành